Pemasangan Kateter Urine Pada Pasien Lawan Jenis Dilihat Dari Sudut Pandang Islam - Fathurrohman Jamil; Aulya Nur Azis; Rimba Aprillia Asmara; Rinda Sipa Nuraeni; Sayyidah Rihhadatul 'Aisy; Trias Syafira; Tedi Supriyadi (Jurnal Keperawatan Galuh, 2025)
The majority of Indonesians are Muslim, as well as medical personnel in hospitals. Meanwhile, many nursing actions are contrary to Islamic norms such as urinary catheters installation in opposite sex patients.  This study aims to understand Islamic rules of urinary catheters installation by opposite sex nurse, limitation and requirements, and nurses experiences in  urinary catheters installation in opposite sex patients. Research design used is qualitative study with case study and collecting data with interview. The informant taken by purposive sampling from nurses at Umar Wirahadikusumah Regional General Hospital and contemporary scholars from Al-Ihsan Modern Islamic Boarding School, An-Nuur Modern Islamic Boarding School, and Pagelaran 2 Islamic Boarding School. Contemporary scholars state that aurat is part of human that must be watched over and properly maintained even during medical treatment, but if it must be done quickly, urinary catheter installation is allowed on some condition such as it’s done without lust, accompanied by patient's mahram, and pure intention of helping. They both prioritize patient's condition and safety. Urinary catheter installation by nurse to opposite sex patients is allowed when same sex nurse is not posible to perform the action. The installation can be done while maintaining patient’s privacy, honor, and belief.